Does cognition have a role in plasticity of "innate behavior"? A perspective from Drosophila - Gorostiza, Ezequiel Axel (2018)
The term innate is usually applied to behaviors commonly characterized as stereotypical reactions to the presence of a specific stimulus. "Innate behaviors", such as escape responses or taxes, are described as inborn, almost inflexible and automatic, with no cognitive demand. However, recent research has shown that many of these behaviors are more complex than initially imagined, and could be largely modulated by context, internal state, and experience, causing in some cases the opposite of the action expected. These processes are sufficient to put the notion of "innate behaviors" as stereotypic and automatic responses under critical scrutiny. This scrutiny has opened the possibility that some cognitive components are involved in ?innate behaviors?. Moreover, the fact that biogenic amines, known for their role in cognitive processes, are emerging as key players in such "innate behaviors" also points in this direction. Here, I present some examples from Drosophila melanogaster supporting a more cognitive interpretation of these behaviors.